Acid for the children : a memoir - Flea (Musician) (Grand Central Publishing, 2019)
The co-founder of the Red Hot Chili Peppers chronicles his life from his birth in Australia and upbringing on the streets of Los Angeles through his rise to Rock and Roll Hall of Fame inductee.